CLEAN DEVELOPMENT MECHANISM (CDM) AND RENEWABLE ENERGY PROJECTS: POTENTIAL REVENUE WHILST PROMOTING SUSTAINABLE DEVELOPMENT - hodl, verania (185P -3466)
This paper explores examples of on going small scale renewable energy CDM projects. The picture of expected revenue and community s benefits resulted from those projects are described. Numbers of CERs requested and issued are selected shown. Bundling several small-scale CDM projects that not exceed a total of 15 MW is described. This paper emphasis the importance of community participatory and explorative approaches in identification of local potentials as well as in conducting feasibility assessments.